The Vine Project: Shaping Your Ministry Culture Around Disciple-Making - Qorry Nisabella (Jurnal Amanat Agung, 2020)
Tinjauan Buku The Vine Project: Shaping Your Ministry Culture Around Disciple-Making. (Youngstown: Matthias Media, 2016). 355 halaman. ISBN 1922206946